Experimental Determination, Modeling, and Simulation of Nonlinear Thermal Effects in Bipolar Transistors under Static Conditions: A Critical Review and Update - Vincenzo d’Alessandro; Antonio Pio Catalano; Ciro Scognamillo; Markus Müller; Michael Schröter; Peter J. Zampardi; Lorenzo Codecasa (Energies, 2022)
This paper presents a comprehensive overview of nonlinear thermal effects in bipolar transistors under static conditions. The influence of these effects on the thermal resistance is theoretically explained and analytically modeled using the single-semiconductor assumption. A detailed review of experimental techniques to extract the thermal resistance as a function of backside temperature and/or dissipated power from DC measurements is provided; advantages, underlying approximations, and limitations of all methods are clarified, and guidelines for their correct application are given. Accurate FEM thermal simulations of an InGaP/GaAs and a Si/SiGe HBT are performed to verify the accuracy of the single-semiconductor theory. The thermal resistance formulations employed in the most popular compact bipolar transistor models for circuit simulators are investigated, and it is found that they do not properly describe nonlinear thermal effects. Alternative implementations of the more accurate single-semiconductor theory are then proposed for the future versions of the compact models.